1958
DOI: 10.1104/pp.33.3.218
|View full text |Cite
|
Sign up to set email alerts
|

Fat Utilization and Composition in Germinating Cotton Seeds.

Abstract: Diminuition of the fat reserve and concomitant increase of carbohydrate during germination of oil seeds have been well established (3,7,10,11,12,13,16). Few studies, however, have compared illuminated and unilluminated seedlings, or have controlled the environmental conditions to the degree necessary for calculation of a rate constant and for prediction of fat content at various stages of growth. MacLachlan (9) found a greater utilization of fat during soybean germination in the light than in the dark. He conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1964
1964
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This is clear from the data presented here where control of enzyme activity was achieved by raising the pH and by adding pCMB. White (19), and Crombie and Comber (6) accomplished the same purpose by boiling the seed before maceration. Ching (4) also shows a low FFA in Douglas fir seeds; in this instance it apparently was not necessary to destroy activity before maceration.…”
Section: Discussionmentioning
confidence: 99%
“…This is clear from the data presented here where control of enzyme activity was achieved by raising the pH and by adding pCMB. White (19), and Crombie and Comber (6) accomplished the same purpose by boiling the seed before maceration. Ching (4) also shows a low FFA in Douglas fir seeds; in this instance it apparently was not necessary to destroy activity before maceration.…”
Section: Discussionmentioning
confidence: 99%
“…During this dependency period, only about half of the seed's lipid content is used by the developing seedling. The long dependency and limited recycling of stored reserves contrasts markedly with the rapid depletion (4 to 14 d from germination) of reserve materials and the short dependency in many plants (Ching, 1963(Ching, , 1966Miller, 1938;Von Ohlen, 1931;Varner, 1965;White, 1958). During the dependency period, radicle (taproot) elongation is 20 to 25 cm before the epicotyl emerges, whereby conferring a competitive advantage in the acquisition of soil moisture during the critical germination period.…”
Section: Tree Growth and Pecan Adaptation To River Bottom Landmentioning
confidence: 99%
“…acids produced may vary during, for example, aging of potato tuber tissue (Willemot and Stumpf [43]) or alteration of oxygen available to plants (Harris and James [14]). White (42) found that cotton seeds deplete stored linoleic and saturated acids faster than oleic whereas germinating watermelon studied by Hardman and Crombie (13) showed a relatively unspecific breakdown of stored fat.…”
mentioning
confidence: 99%